EFFECT OF PHARMACIST COUNSELING ON THERAPEUTIC OUTCOMES OF HYPERTENSIVE PATIENTS IN THE INTERNAL DISEASE CLINIC AT RSUD KRATON PEKALONGAN DISTRICT - Anita Budi Mulyasih; Djoko Wahyono; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Increasing prevalence of hypertension in almost countries cause by the changes of life style such as smoking,obesity,limitness of physical activity and psychosocial stress. Comprehensive and intensive treatment could bedone to control blood pressure. Patient understanding, knowledge and adherence expected to increase with correctdruginformation given by pharmacist. This study aimed to determine the effect of pharmacist counseling ontherapeutic outcomes and patient adherence. The correlation between therapeutic outcomes and patient adherencealso was studied. of outpatients hypertensive in the internal disease clinic at RSUD Kraton Pekalongan District. This research was experimental intervention with pre-post intervention with randomized without matching. Data was collected by prospective method. The control group given a leaflet at the first month, and the intervention group given a leaflet at the first month and counseling every early month, during 3 months. There was 75 patients as respondent of this research. The intervention group (N=39) experienced a significantdecrease in blood pressure at the end of the study, on systolic amounted 11.28±8.33 mmHg [P=0.000(P<0.05)] anddiastolic amounted 7.18±6.86 mmHg [P=0.000(P<0.05)], whereas in the control group (N=36) did not experiencea significant decrease in blood pressure is systolic amounted 2.22±10.45 mmHg [P=0.203(P>0.05)] and diastolicamounted 0.28±6.09 mmHg [P=0.782(P>0.05)]. Adherence of patients as measured by MMAS scale. The interventiongroup had better adherence than the control group (33.33% : 2.78%). There was have correlation a means betweenMMAS score with change of systolic (P=0.019; r=0.270) and diastolic (P=0.001; r=0.372) which positive direction. It was concluded that counseling had an effect on adherence positively in the intervention group better than the controlgroup and decreasing systolic and diastolic blood pressure until reach targets. There was a close correlation betweendecrease in blood pressure with MMAS score in hypertensive patients. Key Words : Hypertension, counseling, outpatient, adherence